A dynamo explanation for Mercury's anomalous magnetic field. Issue 12 (19th June 2014) - Cao, Hao; Aurnou, Jonathan M.; Wicht, Johannes; Dietrich, Wieland; Soderlund, Krista M.; Russell, Christopher T.
Abstract Recent MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) measurements have shown that Mercury's magnetic field is axial‐dominant, yet strongly asymmetric with respect to the equator: the field strength in the Northern Hemisphere is approximately 3 times stronger than that in the Southern Hemisphere. Here we show that convective dynamo models driven by volumetric buoyancy with north‐south symmetric thermal boundaries are capable of generating quasi‐steady north‐south asymmetric magnetic fields similar to Mercury's. This symmetry breaking is promoted and stabilized when the core‐mantle boundary heat flux is higher at the equator than at high latitudes. The equatorially asymmetric magnetic field generation in our dynamo models corresponds to equatorially asymmetric kinetic helicity, which results from mutual excitation of two different modes of columnar convection. Our dynamo model can be tested by future assessment of Mercury's magnetic field from MESSENGER and BepiColombo as well as through investigations on Mercury's lower mantle temperature heterogeneity and buoyancy forcing in Mercury's core.